Web-Based Information System Of Sales And Purchase Of Msme Products In The Sidorejo Hilir Village Office - Sitorus, Elma Sari; Rajagukguk, Denni M.; Lumbanbatu, Maristella J. (Jurnal Komputer Indonesia (Ju-Komi), 2022)
In Sidorejo Hilir Village, there is an outlet that sells MSME food and beverage products which are managed by the lurah office staff, in the process of recording sales, purchases and stock of goods is still done manually or written into a book, which often results in incorrect recording of inventory. as well as sales and purchase reports. The method used is observation, interviews and literature methods to complete the data needed in compiling the Final Project. For this reason, a sales and purchasing information system is needed that can assist staff in recording sales reports and inventory reports, so that they are faster, more efficient and effective.